Comodulation Masking Release (CMR) in Children and the Influence of Reading Status. - Zettler, Cynthia M.; Sevcik, Rose A.; Morris, Robin D.; Clarkson, Marsha G. (Journal of Speech, Language & Hearing Research, 2008)
Purpose: Research suggests that children with reading disabilities (RD) have difficulty processing temporal and spectral components of sounds. Comodulafion masking release (CMR) measures a listener's ability to use temporal and spectral information in noise to identify a signal. The purpose of this study was to determine whether children with RD had difficulty identifying a signal in CMR stimuli. Child and adult performance was compared to assess the development of CMR. Method: Eighty-one 7- to 10-year-old children (30 with and 51 without RD) and 20 adults without RD listened to CMR stimuli through headphones. The difference between reference and modulated masker thresholds provided a measure of CMR. Results: Hierarchical regression analyses indicated that reading status did not predict thresholds or CMR. An analysis of variance revealed significantly less CMR for children than for adults. Conclusions: This research does not support the hypothesis that children with RD have difficulty processing temporal and spectral auditory information as measured by the CMR paradigm. In contrast with some previous research (K. Veloso, J. Hall, & J. Grose, 1990), this study suggests that CMR is continuing to develop beyond 10 years of age. Future research using a CMR paradigm with older children (10-16 years of age) would further illuminate the developmental picture of CMR. Reprinted by permission of the publisher.